Evaluasi Kelayakan Sumber Air Baku pada Kolong yang Tercemar Tailing dari Aktivitas Remaining Bijih Timah - Janiar Pitulima; Irvani Irvani (PROMINE, 2016)
Land Clearing for tin ore mining on Bangka Island for hundreds of years produces mine ponds calledkolong. Water resources at the old age kolong have been utilized by the community as a source ofdomestic water, including the source of water by Regional Drinking Water Company (PDAM). Illegal tinore mining since 2000 until now by the community (unconventional mining) has caused pollution ofPDAM water resources by mining waste of tailings. Primary and secondary data collection has beendone on Kolong PDAM Tirta Bangka, PDAM Tirta Pinang and PDAM Sejiran Setason. Physical datacollection of water and sediments to obtain parameters of temperature, smell, soluble and suspendedsolids and turbidity. Chemical analysis of water and sediments including pH, heavy metal of Fe, Al, Pb,and Cu using AAS and XRF. Feasibility evaluation of the water using Permenkes RI Number907/Menkes/SK/VII/2002. Heavy metals were founded on all the water of kolong are Fe, Al, Cu andPb. Heavy metal in sediment are Fe, Cu, Pb, Sn and As. Kolong Merawang has a large distribution ofFe, Al, Cu and Pb in water and sediment. Al metal exceeds the threshold in Kolong Merawang andPedindang (1.01 mg/L and 0.35 mg/L). The Fe composition at all kolong sediment is very large innumber. The distribution of dissolved Pb metal in water exceeds the threshold at all kolong, especiallyon sediment of Kolong Merawang and Pedindang. Water resources at all kolong have met in physicalfeasibility but exclude their chemistry